Morphological and lectin histochemical characteristics of spleen under the experimental application of H1-histamine receptor blockers. - Dudok, O. V.; Yashchenko, A. M.; Lutsyk, O. D. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. It is well known that histamine modulate immunocompetent cells cooperation, since plenty of them expose H- and H2- receptors for this biogenic amine. However, the influence of synthetic blockers of these receptors on the structure and function of the spleen – the immune system organ – remains obscure. Objective. To investigate the influence of widely used H1-receptor blocker Loratadine on the microstructure and lectin histochemistry characteristics of a rat spleen. Methods. Daily intragastric insertion of Loratadine at a dose of 0.15 mg/kg was maintained for 30 days. Thereafter (on days 10th, 30th of experiment and on days 10th, 20th and 30th after its completion) tissue samples of spleen were excised and subjected to general morphology and lectin histochemistry investigation. Results. On the early stages of Loratadine administration it was detected the increased white pulp content. Further changes included the appearance of germinative centers in lymphoid follicles with simultaneous compactization of periarterial zones. Lectin histochemistry revealed the accumulation of dendritic cells, which were selectively labeled by PNA and GNA, while WGA demonstrated its suitability for differential staining of white and red pulp in the rat spleen. Conclusion. Prolonged Loratadine administration induce antigenic stimulation of the spleen. Lectins PNA and GNA can be recommended for selective labeling of activated dendritic cells, WGA – for differential staining of white and red pulp of the rat spleen.